A Note on the Poly-Bernoulli Polynomials of the Second Kind - Sang Jo Yun; Jin-Woo Park (Journal of Function Spaces)
In this paper, we define the poly-Bernoulli polynomials of the second kind by using the polyexponential function and find some interesting identities of those polynomials. In addition, we define unipoly-Bernoulli polynomials of the second kind and study some properties of those polynomials.